Nurse led, home based self help treatment for patients in primary care with chronic fatigue syndrome: randomised controlled trial. (23rd April 2010) - Wearden, Alison J; Dowrick, Christopher; Chew-Graham, Carolyn; Bentall, Richard P; Morriss, Richard K; Peters, Sarah; Riste, Lisa; Richardson, Gerry; Lovell, Karina; Dunn, Graham
Abstract : Objective To evaluate the effectiveness of home delivered pragmatic rehabilitation—a programme of gradually increasing activity designed collaboratively by the patient and the therapist—and supportive listening—an approach based on non-directive counselling—for patients in primary care with chronic fatigue syndrome/myalgic encephalomyelitis or encephalitis (CFS/ME). Design Single blind, randomised, controlled trial. Setting 186 general practices across the north west of England between February 2005 and May 2007. Participants 296 patients aged 18 or over with CFS/ME (median illness duration seven years) diagnosed using the Oxford criteria. Interventions Participants were randomly allocated to pragmatic rehabilitation, supportive listening, or general practitioner treatment as usual. Both therapies were delivered at home in 10 sessions over 18 weeks by one of three adult specialty general nurses who had received four months' training, including supervised practice, in each of the interventions. GP treatment as usual was unconstrained except that patients were not to be referred for systematic psychological therapies during the treatment period. Main outcome measures The primary clinical outcomes were fatigue and physical functioning at the end of treatment (20 weeks) and 70 weeks from recruitment compared with GP treatment as usual. Lower fatigue scores and higher physical functioning scores denote better outcomes. Results A total of 257 (87%) of the 296 patients who entered the trial were assessed at 70 weeks, the primary outcome point. Analysis was on an intention to treat basis, with robust treatment effects estimated after adjustment for missing data using probability weights. Immediately after treatment (at 20 weeks), patients allocated to pragmatic rehabilitation (n=95) had significantly improved fatigue (effect estimate -1.18, 95% confidence interval -2.18 to -0.18; P=0.021) but not physical functioning (-0.18, 95% CI -5.88 to +5.52; P=0.950) compared with patients allocated to treatment as usual (n=100). At one year after finishing treatment (70 weeks), there were no statistically significant differences in fatigue or physical functioning between patients allocated to pragmatic rehabilitation and those on treatment as usual (-1.00, 95% CI -2.10 to +0.11; P=0.076 and +2.57, 95% CI 3.90 to +9.03; P=0.435). At 20 weeks, patients allocated to supportive listening (n=101) had poorer physical functioning than those allocated to treatment as usual (-7.54, 95% CI -12.76 to -2.33; P=0.005) and no difference in fatigue. At 70 weeks, patients allocated to supportive listening did not differ significantly from those allocated to treatment as usual on either primary outcome. Conclusions For patients with CFS/ME in primary care, pragmatic rehabilitation delivered by trained nurse therapists improves fatigue in the short term compared with unconstrained GP treatment as usual, but the effect is small and not statistically significant at one year follow-up. Supportive listening delivered by trained nurse therapists is not an effective treatment for CFS/ME. Trial registration International Standard Randomised Controlled Trial Number IRCTN74156610.